Analisis Kegiatan Komunikasi Pemasaran Restoran Bacco Wine Culture Jakarta - Wahyuni, Diana Lohita; Masyurah, Anabel; Suwuh, Lydia (JURNAL ADMINISTRASI BISNIS, 2022)
This study aims to understand and analyze the marketing communication activities carried out by Bacco Wine Culture. The proliferation of similar restaurants in Jakarta requires Bacco Wine Culture to set a strategy on how to win the competition. One strategy to win today’s competition is to increase marketing activities. The methodology used in this study is a descriptive methodology with a qualitative approach. The results of this study indicate that in its marketing communication activities Bacco Wine Culture has carried out 8 marketing communication mixes, but the marketing communication activities carried out are sales promotion, events and experiences, direct marketing, interactive marketing, word of mouth marketing, and personal selling. Bacco Wine Culture has carried out marketing communications using Lasswell’s communication theory, namely Who, Says What, In Which Channel, To Whom, and With What Effect